2014
DOI: 10.1101/gad.235473.113
|View full text |Cite
|
Sign up to set email alerts
|

The R-spondin/Lgr5/Rnf43 module: regulator of Wnt signal strength

Abstract: Lgr5 was originally discovered as a common Wnt target gene in adult intestinal crypts and colon cancer. It was subsequently identified as an exquisite marker of multiple Wnt-driven adult stem cell types. Lgr5 and its homologs, Lgr4 and Lgr6, constitute the receptors for R-spondins, potent Wnt signal enhancers and stem cell growth factors. The Lgr5/R-spondin complex acts by neutralizing Rnf43 and Znrf3, two transmembrane E3 ligases that remove Wnt receptors from the stem cell surface. Rnf43/Znrf3 are themselves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
487
3
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 548 publications
(534 citation statements)
references
References 118 publications
10
487
3
1
Order By: Relevance
“…Lgr5 + cells in the GER do not contribute significantly to the regeneration of IBCs and IPhCs, a surprising result given that Lgr5 is a marker of stem cells in other tissues (59)(60)(61)(62) and that Lgr5 + cells proliferate and transdifferentiate into HCs after genetic manipulations in the neonatal organ of Corti (34,38,40). However, we found that other cells in the GER, targeted with GlastCreER T induced with tamoxifen at P0 and P1, are required for the replacement of at least a fraction of IBCs/IPhCs.…”
Section: Discussionmentioning
confidence: 99%
“…Lgr5 + cells in the GER do not contribute significantly to the regeneration of IBCs and IPhCs, a surprising result given that Lgr5 is a marker of stem cells in other tissues (59)(60)(61)(62) and that Lgr5 + cells proliferate and transdifferentiate into HCs after genetic manipulations in the neonatal organ of Corti (34,38,40). However, we found that other cells in the GER, targeted with GlastCreER T induced with tamoxifen at P0 and P1, are required for the replacement of at least a fraction of IBCs/IPhCs.…”
Section: Discussionmentioning
confidence: 99%
“…It functionally acts as a coenhancer of Wnt signaling, and co-operates with Wntmediated canonical pathway activation in ISCs through regulation of the E3-ligase Rnf43 [17,18]. Accordingly, a number of genes regulated downstream of the canonical Wnt pathway, such as ASCL2 [19,20], have been assigned and proved to be ISC-specific genes as well.…”
Section: Homeostasis Of the Normal Intestinal Epitheliamentioning
confidence: 99%
“…52, reviewed in ref. 53). Their mechanism of action has recently been elucidated, and importantly, cancer-associated gain-of-function mutations have been identified.…”
Section: R-spondin Translocations and Gene Amplificationmentioning
confidence: 99%